FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Karen Patricia; Viriany Viriany (Jurnal Paradigma Akuntansi, 2026)
The purpose of this study was to determine the effect of profitability and liquidity on firm value in the food and beverage subsector listed on the Indonesia Stock Exchange from 2019 to 2021, with company size acting as a moderating variable. Purposive sampling was used to select the sample, which included valid data from fourteen companies. The data processing technique employs moderation regression analysis and classic assumptions, which are aided by Eviews version 12. According to the findings of this study, profitability as an independent variable has a negative and significant impact on dependent variable, firm value, whereas liquidity has a positive but insignificant impact on the dependent variable, firm value. Meanwhile, company size can moderate the impact of profitability on company value, but it cannot moderate the impact of liquidity on company value. This research focuses on the need to increase the company's ability to generate profits in order to grow the company's size and attract investors.